Optimizing the Utilization of Multiplex PCR Respiratory Panels at Two Emergency Departments Over Three Consecutive Influenza Seasons. (21st September 2018) - Cho, Joseph; Matushek, Scott; Charnot-Katsikas, Angella
Abstract: Acute respiratory infections (ARIs) are a major reason for emergency department (ED) visits each year. Multiplex PCR respiratory panels aid in accurate, timely, and cost-effective diagnosis of ARI, and clinical pathologists play a significant role in patient care by guiding the appropriate use of such laboratory tests. This study compared differences in the number of targeted (IRP) vs extended (RBVP) respiratory panels ordered by adult and pediatric ED physicians over three consecutive influenza seasons. The IRP is designed to detect influenza A and B and respiratory syncytial virus (RSV), while the RBVP detects 20 infectious respiratory pathogens, including those detected by the IRP. Different guidance approaches were taken prior to each influenza season by the clinical pathology team to steer utilization of the most appropriate respiratory panel. Prior to influenza season 1, an email bulletin was sent to all ED physicians to notify them of the two available respiratory panels and to encourage ordering the IRP when influenza or RSV was suspected. Prior to influenza season 2, a similar email bulletin was again sent to all ED physicians, and weekly updates of the pathogens identified by the respiratory panels were provided. Prior to influenza season 3, the clinical pathology team met with the directors of the adult and pediatric EDs and implemented changes to the ED's "Quick Order List" by adding the IRP to the menu next to the RBVP. The ED directors also sent email bulletins to the ED physicians encouraging the use of the IRP when influenza or RSV was suspected and noting the cost differential between the two tests. The ratio of IRP:RBVP ordered by the adult ED during influenza season 3 was significantly higher than in the prior two seasons: 910:993 in season 3 compared to 295:1, 659 and 339:1, 839 in seasons 1 and 2 ( P < .0001). A similar significant increase in IRP:RBVP ratio was observed for the pediatric ED during season 3 compared to seasons 1 and 2; 58:892 during influenza season 3 vs 17:1, 301 in season 1 and 35:1, 212 in season 2 ( P < .0001). Notably, the combined incidence of influenza in the adult and pediatric EDs was 278, 348, and 515 during seasons 1, 2, and 3, respectively. Along with the higher incidence of influenza in season 3 making it a particularly severe season (data still accruing), our preliminary findings suggest that engaging key clinical leaders directly may be a more effective strategy in optimizing the appropriate utilization of respiratory panels compared to notifications via email or providing incidence data, regardless of frequency. This study also suggests that simple changes in communication and in lab test ordering menus can significantly contribute to the frequency of a lab test being ordered, thus guiding appropriate test utilization.